Estrus and early pregnancy in sows weaned at less than 11 or more than 23 days: effects of vitamin a and gonadotropin treatments - Tonn, S.; Groothius, P.; Boese, B.; Blair, R.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The problem of reduced reproductive performance in sows weaned at 5 to 11 days (early weaned) after farrowing was assessed by comparing estrous and embryonic traits in these sows and others weaned at 23 to 31 days postpartum. The effects of treatment of both groups of sows with PG600 and vitamin A also were studied. PG600 increased the number of sows in estrus regardless of weaning age and reduced the interval from weaning to estrus for early-weaned sows. Both vitamin A and PG600 tended to increase the number of embryos recovered at 11.5 days after the onset of estrus.
Keywords: Swine; Estrus; Embryo survival; PG600; Gonadotropins,; Vitamin A